Energy of the So-called "Third Transition" and Intensity of Spin-forbidden Band in Chromium(III) complex of diethylamino-ethanethiol - P.C. Jain (CHIMIA)
The electronic spectra of chromium(III) complex of diethylamino-ethanethiol have been recorded. The value of Racah’s interelectronic repulsion parameter (B) has been evaluated and employed for the theoretical calculation of extra bands. The oscillator strength ratio of spin-forbidden to spin-allowed bands with “intensity stealing” has also been calculated.